SIA-IgG confers poor prognosis and represents a novel therapeutic target in breast cancer. Issue 4 (1st April 2022) - Zhang, Man; Zheng, Jinhua; Guo, Junying; Zhang, Qiujin; Du, Juan; Zhao, Xiangfeng; Wang, Zhihua; Liao, Qinyuan
ABSTRACT: The incidence rate of breast cancer is the highest in the world, and major problem in the clinical treatment is the therapy resistance of breast cancer stem cells (CSCs). Thus, new therapeutic approaches targeting breast CSCs are needed. Our previous study demonstrated cancer-derived sialylated IgG (SIA-IgG) is highly expressed in cancer cells with stem/progenitor features. Furthermore, a high frequency of SIA-IgG in breast cancer tissue predicted metastasis and correlated with poor prognosis factors, and depletion of IgG in breast cancer leads to lower malignancy of cancer cells, suggesting SIA-IgG could be a potential therapeutic target in breast cancer. In this study, we first investigated the relationship of SIA-IgG expression with the clinicopathological characteristics and clinical prognosis of breast carcinoma patients, and the data confirmed that the expression of SIA-IgG confers poor prognosis in breast cancer. Successively, by using a monoclonal antibody specifically against SIA-IgG, we targeted SIA-IgG on the surface of MDA-MB-231 cells and detected their functional changes, and the results suggested SIA-IgG to be a promising antibody therapeutic target in breast cancer. In addition, we explored the mechanism of action at the molecular level of SIA-IgG on breast cancer cell, the findings suggest that SIA-IgG promotes proliferation, metastasis, and invasion of breast cancer cells through the Wnt /β-catenin signaling pathway. Developing therapeutic antibody needs effective therapeutic target, and the antibody should better be a monoclonal antibody with high affinity and high specificity. This study provides a potential prognostic marker and a novel therapeutic target for breast cancer. GRAPHICAL ABSTRACT: uf0001